Flow boiling heat transfer enhancement via micro-pin-fins/ZnO nanorods hierarchical surface. (April 2023) - Liu, Lei; Yu, Lingmin; Yuan, Bo; Liu, Bin; Wei, Jinjia
Highlights: ZnO nanorods are synthesized on micro-pin-fins by a simple and inexpensive method. Morphology, chemical composition and wickability of the hierarchical surface are characterized. Significant improvement of flow boiling heat transfer performance is achieved. Mechanism of the hierarchical surface in improving heat transfer performance is analysed. Abstract: In this study, ZnO nanorods were synthesized on micro-pin-fins by a simple and inexpensive aqueous solution method for flow boiling heat transfer enhancement. The morphology, chemical composition and wickability of the micro/nano hierarchical surface (PF+NR) were characterized. The heat transfer performance of PF+NR was investigated under various flow velocities together with a micro-pin-finned surface (PF), a ZnO nanorod-coated surface (NR) and a smooth surface (S). The results indicated that the boiling performance is improved significantly by the hierarchical surface and demonstrated a synergism between the microstructure and the nanostructure. The maximum boiling heat transfer coefficient of PF+NR is increased by 63%, 76%, and 158% compared with PF, NR and S, respectively. The critical heat flux is also increased by 31%, 33%, and 74%, respectively. The onset of nucleate boiling temperature of PF+NR is decreased compared with that of the other surfaces. The comprehensive improvement of boiling heat transfer performance is attributed to the cooperation of structures in different scales: the nanorods provide abundant nucleation sites, and the micro-pin-fins improve the liquid replenishment capacity and suppress the lateral coalescence of large bubbles at high heat fluxes. Graphical abstract: Image, graphical abstract